Preparation method of anion exchange membrane and anion exchange membrane
By preparing a composite membrane of propylsilsesquioxane with quaternized polysulfone with imidazolium, the problem of low stability of the anion exchange membrane is solved, the electrolytic efficiency and service life is improved, and the problem of low power in AEM electrolytic water technology is overcome.
Patent Information
- Application Number
- CN202311267153.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The stability of the anion exchange membrane is low, resulting in low electrolytic efficiency.
Anion exchange membrane was prepared by preparing grafted imidazolium propylsilsesquioxane and completely dissolved with quaternized polysulfone and evaporated to improve the alkali resistance and thermomechanical stability of the membrane.
It improves the ion conductivity of the anion exchange membrane, saves energy, and extends its service life, overcoming the problem of low power application in AEM electrolytic technology after filming.
Smart Images

Figure CN119708577A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a preparation method of an anion exchange membrane and the anion exchange membrane. Background Art
[0002] Hydrogen energy is regarded as an ideal clean energy source, and it is particularly important to find a simple, efficient and cheap method to produce hydrogen. Among the many hydrogen production technologies, water electrolysis is an important way to produce green hydrogen. The main technical routes currently include alkaline water hydrogen production, proton exchange membrane electrolysis hydrogen production, and high-temperature solid oxide electrolysis hydrogen production.
[0003] Among them, alkaline water hydrogen production has irreplaceable advantages in large-scale and cheap hydrogen production, but the main problem it faces is the excessively high energy consumption of electrolysis. Therefore, the use of high-performance electrodes is an effective means to reduce energy consumption.
[0004] In order to improve the performance of hydrogen production by electrolysis, it is a technical problem that needs to be solved urgently to manufacture hybrid membranes by adding suitable inorganic fillers into the membranes to improve the overall properties of the membranes, such as water absorption, electrical conductivity and thermomechanical stability. Summary of the invention
[0005] In view of this, the present invention aims to solve the technical problem that the current anion exchange membrane has low stability, resulting in low electrolysis efficiency.
[0006] A first aspect of the present invention provides a method for preparing an anion exchange membrane.
[0007] A second aspect of the present invention provides an anion exchange membrane.
[0008] Specifically, the present invention is achieved through the following technical solutions:
[0009] The first technical solution of the present invention provides a method for preparing an anion exchange membrane, comprising: preparing octachloropropyl silsesquioxane; preparing octaiodopropyl silsesquioxane based on octachloropropyl silsesquioxane; preparing imidazolium-grafted propyl silsesquioxane based on octaiodopropyl silsesquioxane; preparing anion exchange membrane based on imidazolium-grafted propyl silsesquioxane and quaternized polysulfone.
[0010] The preparation method of the anion exchange membrane of the present invention comprises: first preparing octachloropropyl silsesquioxane, replacing the chlorine element on the octachloropropyl silsesquioxane with iodine element to obtain octaiodopropyl silsesquioxane, and finally replacing the iodine element with imidazole group to obtain propyl silsesquioxane grafted with imidazole group. The present invention uses propyl silsesquioxane grafted with imidazolium as raw material, so that the prepared anion exchange membrane contains a large amount of imidazole groups, thereby having a small resistance to hydroxyl ion conduction, improving ion conductivity, saving energy, and in addition, the imidazole group has good thermomechanical stability, so that the alkali resistance stability and excellent thermomechanical stability of the anion exchange membrane can be improved, and the service life can be improved. In addition, since the present invention is an ion exchange membrane prepared by completely dissolving and evaporating propyl silsesquioxane grafted with imidazolium and quaternized polysulfone, the problem of low power in AEM electrolysis water technology after the quaternized polysulfone (QPSU) material is applied to the membrane.
[0011] In the above technical scheme, the step of preparing octachloropropyl silsesquioxane includes: mixing methanol and hydrochloric acid solution to obtain a first mixture, cooling the first mixture to a first preset temperature, adding 3-chloropropyltrimethoxysilane and a catalyst to the first mixture, and stirring for a first preset time, obtaining a generated precipitate, and washing the precipitate with methanol to obtain octachloropropyl silsesquioxane.
[0012] In this technical solution, 3-chloropropyltrimethoxysilane can undergo polymerization reaction under the action of a catalyst to form octachloropropylsilsesquioxane.
[0013] In the above technical solution, in the step of washing the precipitate with methanol to obtain octachloropropylsilsesquioxane, the washing times are greater than or equal to 3 times.
[0014] In this technical solution, the precipitate is washed with methanol at least three times, so that the purity of octachloropropylsilsesquioxane can be improved.
[0015] In the above technical solution, the first preset temperature is greater than or equal to 0° C. and less than or equal to 5° C.; the first preset time is greater than or equal to 40 hours and less than or equal to 60 hours.
[0016] In this technical solution, the first preset temperature is greater than or equal to 0°C and less than or equal to 5°C; further, the first preset temperature is equal to 0°C, and by controlling the solution temperature, side reactions can be prevented and the crosslinking rate of octachloropropyl silsesquioxane can be increased. The first preset time is greater than or equal to 40h and less than or equal to 60h, and further, the first preset time is equal to 50h, and the temperature of the mixed solution of methanol and hydrochloric acid solution and the stirring time can be controlled to ensure the yield of octachloropropyl silsesquioxane.
[0017] In the above technical solution, the catalyst includes di-n-butyltin dilaurate.
[0018] In the above technical solution, the mass ratio of the catalyst to the mass ratio of 3-chloropropyltrimethoxysilane is greater than or equal to 1:120 and less than or equal to 1:60.
[0019] In this technical solution, the mass ratio of the catalyst to 3-chloropropyltrimethoxysilane is controlled, so that the polymerization rate of 3-chloropropyltrimethoxysilane can be guaranteed, the yield of octachloropropylsilsesquioxane can be increased, and an excessive amount of catalyst and waste of materials can be avoided.
[0020] In the above technical solution, the mass fraction of hydrochloric acid in the hydrochloric acid solution is greater than or equal to 30% and less than or equal to 40%.
[0021] In the above technical scheme, the step of preparing octaiodopropyl silsesquioxane based on octachloropropyl silsesquioxane includes: dissolving octachloropropyl silsesquioxane and iodine salt in tetrahydrofuran to obtain a second mixture, and continuously stirring the second mixture for a second preset time under the condition of a second preset temperature, evaporating the tetrahydrofuran in the second mixture to obtain a first product, and extracting octaiodopropyl silsesquioxane from the first product.
[0022] In this technical solution, octachloropropyl silsesquioxane and iodine salt are dissolved in tetrahydrofuran, and the mixture is stirred, so that the iodine element replaces the chlorine element on the octachloropropyl silsesquioxane to obtain octaiodopropyl silsesquioxane. The first product mainly includes the generated octaiodopropyl silsesquioxane and the iodine salt that does not participate in the reaction.
[0023] In the above technical scheme, the step of extracting octaiodopropyl silsesquioxane from the first product includes: putting the first product into a mixed solution of chloroform and water to form an organic layer and an aqueous layer, separating the organic layer and passing sodium sulfate and sodium thiosulfate into the organic layer to remove the chloroform in the organic layer to obtain octaiodopropyl silsesquioxane.
[0024] In this technical solution, the first product is extracted with a mixture of water and chloroform. Since water and chloroform are immiscible, the octaiodopropyl silsesquioxane in the first product is dissolved in chloroform, while the remaining impurities are dissolved in water. The organic layer is then separated and passed through a column filled with a mixture of sodium sulfate and sodium thiosulfate to remove unreacted iodide. Finally, the chloroform is evaporated to obtain octaiodopropyl silsesquioxane.
[0025] In the above technical solution, the iodized salt is sodium iodide.
[0026] In the above technical solution, the mass ratio of octachloropropylsilsesquioxane to sodium iodide is greater than or equal to 1:3 and less than or equal to 1:1.
[0027] In this technical solution, by controlling the mass ratio of octachloropropyl silsesquioxane to sodium iodide, the iodine element can better replace the chlorine element in the octachloropropyl silsesquioxane, thereby increasing the yield of octaiodopropyl silsesquioxane.
[0028] In the above technical solution, the second preset temperature is greater than or equal to 50° C. and less than or equal to 70° C.; the second preset time is greater than or equal to 60 hours and less than or equal to 80 hours.
[0029] In this technical solution, the reaction temperature and reaction time of octachloropropyl silsesquioxane and iodine salt are controlled to ensure the generation of octaiodopropyl silsesquioxane.
[0030] In the above technical solution, the step of continuously stirring the second mixture at the second preset temperature for the second preset time period is performed in a closed environment without any light.
[0031] In this technical solution, the reaction between octachloropropylsilsesquioxane and iodine salt is controlled to be in dark conditions, so that the generation of octaiodopropylsilsesquioxane can be ensured.
[0032] In the above technical scheme, the step of preparing imidazolium-grafted propyl silsesquioxane based on octaiodopropyl silsesquioxane includes: dissolving octaiodopropyl silsesquioxane in N,N-dimethylformamide under a preset environment, and adding N-methylimidazole dropwise, reacting at a third preset temperature for a third preset time to obtain a third mixture, and vacuum drying the third mixture to obtain imidazolium-grafted propyl silsesquioxane.
[0033] In this technical solution, octaiodopropyl silsesquioxane is dissolved in N,N-dimethylformamide, and N-methylimidazole is added dropwise, so that the imidazole group can replace the iodine element in the octaiodopropyl silsesquioxane to generate imidazolium-grafted propyl silsesquioxane, and then the N,N-dimethylformamide solvent and excess unreacted imidazole are vacuum dried to obtain imidazolium-grafted propyl silsesquioxane.
[0034] In the above technical solution, the preset environment includes a protective gas environment, and further includes a nitrogen environment.
[0035] In this technical solution, the reaction environment of octaiodopropylsilsesquioxane and N-methylimidazole is controlled to be a nitrogen environment, so as to avoid oxygen doping and reduce the grafting effect.
[0036] In the above technical solution, the third preset temperature is greater than or equal to 50°C and less than or equal to 70°C; the third preset time is greater than or equal to 20h and less than or equal to 48h; further, the third preset temperature is equal to 60°C; the third preset time is equal to 24h.
[0037] In this technical solution, by controlling the reaction temperature and reaction time of octaiodopropyl silsesquioxane and N-methylimidazole, the smooth grafting of the imidazole group can be ensured, and the yield of the imidazolium-grafted propyl silsesquioxane can be guaranteed.
[0038] In the above technical solution, the mass ratio of octaiodopropylsilsesquioxane to N-methylimidazole is greater than or equal to 1:15 and less than or equal to 1:3.
[0039] In these technical solutions, the grafting rate of the imidazole group can be ensured by controlling the mass ratio of octaiodopropylsilsesquioxane to N-methylimidazole.
[0040] In the above technical scheme, the steps of preparing an anion exchange membrane based on grafted imidazolium propyl silsesquioxane and quaternized polysulfone include: dissolving the grafted imidazolium propyl silsesquioxane in water to obtain an aqueous solution of grafted imidazolium propyl silsesquioxane; dissolving the quaternized polysulfone in an N,N-dimethylformamide solution, adding the aqueous solution of grafted imidazolium propyl silsesquioxane and stirring for a fourth preset time to obtain a fourth mixture, then pouring the fourth mixture into a culture dish, drying at a fourth preset temperature to obtain a composite membrane, and immersing the composite membrane in a potassium hydroxide solution to obtain an anion exchange membrane.
[0041] In this technical solution, the grafted imidazolium propyl silsesquioxane is first dissolved in water to obtain an aqueous solution of the grafted imidazolium propyl silsesquioxane, and then the quaternized polysulfone is dissolved in an N,N-dimethylformamide solution, and the aqueous solution of the grafted imidazolium propyl silsesquioxane is added at the same time, and stirred for a fourth preset time to obtain a fourth mixture, at which time the quaternized polysulfone and the grafted imidazolium propyl silsesquioxane are completely mixed, and finally the mixture is dried at a fourth preset temperature to remove the N,N-dimethylformamide solution solvent and water to obtain a composite membrane in which the quaternized polysulfone and the grafted imidazolium propyl silsesquioxane are completely mixed, and finally the composite is immersed in a potassium hydroxide solution to obtain an anion exchange membrane, wherein the potassium hydroxide is to convert the benzimidazole group to be positively charged and convert it into an anion exchange membrane.
[0042] In the above technical solution, in the step of drying at the fourth preset temperature, the drying environment is a vacuum environment.
[0043] In the above technical solution, the fourth preset temperature is greater than or equal to 50°C and less than or equal to 70°C; the fourth preset time is greater than or equal to 40h and less than or equal to 72h. Further, the fourth preset temperature is equal to 60°C; the fourth preset time is equal to 48h.
[0044] In this technical solution, controlling the stirring time can make the quaternized polysulfone and the grafted imidazolium propyl silsesquioxane mix evenly, and controlling the drying temperature can ensure that the N,N-dimethylformamide solution solvent and water in the mixture are completely removed to obtain a complex composed of the quaternized polysulfone and the grafted imidazolium propyl silsesquioxane.
[0045] In the above technical solution, in the aqueous solution of imidazolium-grafted propyl silsesquioxane, the mass proportion of imidazolium-grafted propyl silsesquioxane is greater than or equal to 5% and less than or equal to 20%. Further, the mass proportion of imidazolium-grafted propyl silsesquioxane is 15%.
[0046] In the above technical solution, in the potassium hydroxide solution, the molar concentration of potassium hydroxide is greater than or equal to 0.5 mol / L and less than or equal to 1.5 mol / L. Further, the molar concentration of potassium hydroxide is 1 mol / L.
[0047] In this technical solution, the concentration of potassium hydroxide is controlled, so that the conductivity of the anion exchange membrane can be improved.
[0048] In the above technical solution, the quaternized polysulfone includes quaternized polysulfone with chloride ions.
[0049] In the above technical scheme, the quaternary ammonium polysulfone with chloride ions is prepared by the following method: dissolving the polysulfone in chloroform, adding polyoxymethylene and chlorotrimethylsilane to the chloroform to obtain a fifth mixture, adding tin tetrachloride to the fifth mixture to generate chloromethylated polysulfone; dissolving the chloromethylated polysulfone in N,N-dimethylformamide, and adding triethylamine to the N,N-dimethylformamide to generate a second product, drying the second product, and washing the second product with N,N-dimethylformamide and methanol in turn to obtain the quaternary ammonium polysulfone with chloride ions.
[0050] In the technical scheme, when preparing quaternary ammonium polysulfone with chloride ions, 22.6 mmol of polysulfone (PSU) can be weighed and transferred to a three-necked flask, dissolved in a certain amount of chloroform to obtain a clear polymer solution, and then a mixture of 226 mmol of paraformaldehyde and 226 mmol of chlorotrimethylsilane is added as a chloromethylating agent, and stirred continuously at the same time. In the presence of 2.26 mmol of SnCl4, the reaction is carried out at 60°C for 24 hours to generate a large amount of chloromethylated polysulfone product, and then methanol is used to precipitate and separate the chloromethylated polysulfone product, and then the chloromethylated polysulfone product is further washed with water several times until the pH is neutral. Then the product is dried at 60°C for one day to obtain pure chloromethylated polysulfone. After drying, the chloromethylated polysulfone (CMPSU) is transferred to a three-necked flask and dissolved in an appropriate amount of N,N-dimethylformamide. Triethylamine is added to the solution, and a nitrogen atmosphere is maintained during the entire reaction process. The reaction is carried out at 80°C for about 24 hours to obtain a second product and dry it. After drying, the second product is washed with N,N-dimethylformamide and methanol in sequence to obtain pure quaternized polysulfone. Since the ammonium ions in the triethylamine are paired with the chloride ions in the chloromethylated polysulfone in the quaternization step, the quaternized polysulfone prepared by the present invention is also called quaternized polysulfone with chloride ions. Of course, the paired anions in the quaternized polysulfone can be anions such as sulfonate, and the quaternized polysulfone with chloride ions in the present invention means that the anions paired with the quaternized polysulfone are chloride ions.
[0051] The second aspect of the present invention provides an anion exchange membrane. The anion exchange membrane provided by the present invention is prepared according to the method for preparing an anion exchange membrane provided by any technical solution of the first aspect of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0053] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or related technical descriptions are briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0054] Figure 1 One of the schematic diagrams of the preparation process of the method for preparing an anion exchange membrane provided in an embodiment of the present invention;
[0055] Figure 2 A second schematic diagram of the preparation process of the method for preparing an anion exchange membrane provided in an embodiment of the present invention;
[0056] Figure 3 The third schematic diagram of the preparation process of the method for preparing an anion exchange membrane provided in an embodiment of the present invention;
[0057] Figure 4 A fourth schematic diagram of the preparation process of the method for preparing an anion exchange membrane provided in an embodiment of the present invention;
[0058] Figure 5 A transmission electron microscope image of octachloropropylsilsesquioxane in the method for preparing an anion exchange membrane provided by an embodiment of the present invention;
[0059] Figure 6 The infrared spectrum of the quaternized polysulfone with chloride ions provided in the embodiment of the present invention;
[0060] Figure 7 A hydrogen nuclear magnetic resonance spectrum of IM-POSS (i.e., imidazolium-grafted propyl silsesquioxane) provided in an embodiment of the present invention;
[0061] Figure 8 The infrared spectrum of IM-POSS provided by the embodiment of the present invention;
[0062] Fig. 9 A transmission electron microscope photo of IM-POSS provided by an embodiment of the present invention;
[0063] Fig.10 The tensile strength diagram of the anion exchange membranes obtained in the examples and comparative examples of the present invention;
[0064] Fig.11 The XRD data diagram of the anion exchange membrane obtained in the embodiment and the comparative example of the present invention;
[0065] Fig.12 The electron microscope photographs of the anion exchange membranes obtained in the examples and comparative examples of the present invention;
[0066] Fig.13 The basic performance diagram of the anion exchange membrane obtained in the examples and comparative examples of the present invention (including ion conductivity, ion exchange capacity and water absorption);
[0067] Fig.14 This is a basic performance diagram of the anion exchange membrane obtained in the examples and comparative examples of the present invention after oxidation test. DETAILED DESCRIPTION
[0068] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] See also Figure 1 The first aspect of the present invention provides a method for preparing an anion exchange membrane, comprising the following steps:
[0070] S102: preparing octachloropropylsilsesquioxane;
[0071] S104: preparing octaiodopropyl silsesquioxane based on octachloropropyl silsesquioxane;
[0072] S106: Preparation of propyl silsesquioxane grafted with imidazolium based on octaiodopropyl silsesquioxane;
[0073] S108: Preparation of anion exchange membranes based on imidazolium-grafted propylsilsesquioxane and quaternized polysulfone.
[0074] The preparation method of the anion exchange membrane of the present invention comprises: first preparing octachloropropyl silsesquioxane, replacing the chlorine element on the octachloropropyl silsesquioxane with iodine element to obtain octaiodopropyl silsesquioxane, and finally replacing the iodine element with imidazole group to obtain propyl silsesquioxane grafted with imidazole group. The present invention uses propyl silsesquioxane grafted with imidazolium as raw material, so that the prepared anion exchange membrane contains a large amount of imidazole groups, thereby having a small resistance to hydroxyl ion conduction, improving ion conductivity, saving energy, and in addition, the imidazole group has good thermomechanical stability, so that the alkali resistance stability and excellent thermomechanical stability of the anion exchange membrane can be improved, and the service life can be improved. In addition, since the present invention is an ion exchange membrane prepared by completely dissolving and evaporating propyl silsesquioxane grafted with imidazolium and quaternized polysulfone, the problem of low power in AEM electrolysis water technology after the quaternized polysulfone (QPSU) material is applied to the membrane.
[0075] In the above embodiment, the step of preparing octachloropropyl silsesquioxane includes: mixing methanol and hydrochloric acid solution to obtain a first mixture, cooling the first mixture to a first preset temperature, adding 3-chloropropyl trimethoxysilane and a catalyst to the first mixture, stirring the first mixture of 3-chloropropyl trimethoxysilane and the catalyst for a first preset time, obtaining a generated precipitate, and washing the precipitate with methanol to obtain octachloropropyl silsesquioxane, a transmission electron microscope image of which is shown in FIG. Figure 5 .
[0076] In this embodiment, 3-chloropropyltrimethoxysilane can be polymerized under the action of the catalyst to form octachloropropylsilsesquioxane.
[0077] In the above embodiment, in the step of washing the precipitate with methanol to obtain octachloropropylsilsesquioxane, the washing times are greater than or equal to 3 times.
[0078] In this embodiment, the precipitate is washed with methanol at least three times, which can improve the purity of octachloropropylsilsesquioxane.
[0079] In the above embodiment, the first preset temperature is greater than or equal to 0° C. and less than or equal to 5° C.; the first preset time is greater than or equal to 40 hours and less than or equal to 60 hours.
[0080] In this embodiment, the first preset temperature is greater than or equal to 0°C and less than or equal to 5°C; further, the first preset temperature is equal to 0°C, and by controlling the solution temperature, side reactions can be prevented and the cross-linking rate of octachloropropyl silsesquioxane can be increased; the first preset time is greater than or equal to 40h and less than or equal to 60h, and further, the first preset time is equal to 50h, and the temperature of the mixed solution of methanol and hydrochloric acid solution and the stirring time can be controlled to ensure the output of octachloropropyl silsesquioxane.
[0081] In the above embodiment, the catalyst includes di-n-butyltin dilaurate.
[0082] In the above embodiment, the mass ratio of the catalyst to the mass ratio of 3-chloropropyltrimethoxysilane is greater than or equal to 1:120 and less than or equal to 1:60.
[0083] In this embodiment, the mass ratio of the catalyst to 3-chloropropyltrimethoxysilane is controlled, so that the polymerization rate of 3-chloropropyltrimethoxysilane can be guaranteed, the yield of octachloropropylsilsesquioxane can be increased, and an excessive amount of catalyst and waste of materials can be avoided.
[0084] In the above embodiment, in the hydrochloric acid solution, the mass fraction of hydrochloric acid is greater than or equal to 30% and less than or equal to 40%.
[0085] In the above embodiment, the step of preparing octaiodopropyl silsesquioxane based on octachloropropyl silsesquioxane includes: dissolving octachloropropyl silsesquioxane and iodine salt in tetrahydrofuran to obtain a second mixture, and continuously stirring the second mixture for a second preset time under the condition of a second preset temperature, evaporating tetrahydrofuran in the second mixture to obtain a first product, and extracting octaiodopropyl silsesquioxane from the first product.
[0086] In this embodiment, octachloropropyl silsesquioxane and iodine salt are dissolved in tetrahydrofuran and the mixture is stirred, so that the iodine element replaces the chlorine element on the octachloropropyl silsesquioxane to obtain octaiodopropyl silsesquioxane. The first product mainly includes the generated octaiodopropyl silsesquioxane and the iodine salt that does not participate in the reaction.
[0087] In the above embodiment, the step of extracting octaiodopropyl silsesquioxane from the first product includes: putting the first product into a mixed solution of chloroform and water to form an organic layer and an aqueous layer, separating the organic layer and passing sodium sulfate and sodium thiosulfate into the organic layer to remove chloroform in the organic layer to obtain octaiodopropyl silsesquioxane.
[0088] In this embodiment, the first product is extracted with a mixture of water and chloroform. Since water and chloroform are immiscible, the octaiodopropyl silsesquioxane in the first product is dissolved in chloroform, while the remaining impurities are dissolved in water. The organic layer is then separated and passed through a column filled with a mixture of sodium sulfate and sodium thiosulfate to remove unreacted iodide. Finally, the chloroform is evaporated to obtain octaiodopropyl silsesquioxane.
[0089] In the above embodiment, the iodized salt is sodium iodide.
[0090] In the above embodiment, the mass ratio of octachloropropylsilsesquioxane to sodium iodide is greater than or equal to 1:3 and less than or equal to 1:1.
[0091] In this embodiment, by controlling the mass ratio of octachloropropyl silsesquioxane to sodium iodide, the iodine element can better replace the chlorine element in the octachloropropyl silsesquioxane, thereby increasing the yield of octaiodopropyl silsesquioxane.
[0092] In the above embodiment, the second preset temperature is greater than or equal to 50° C. and less than or equal to 70° C.; the second preset time is greater than or equal to 60 hours and less than or equal to 80 hours.
[0093] In this embodiment, the reaction temperature and reaction time of octachloropropylsilsesquioxane and iodine salt are controlled to ensure the generation of octaiodopropylsilsesquioxane.
[0094] In the above embodiment, the step of continuously stirring the second mixture at the second preset temperature for the second preset time period is performed in a closed environment without any light.
[0095] In this embodiment, the reaction of octachloropropylsilsesquioxane and iodine salt is controlled to be in the dark, so as to ensure the generation of octaiodopropylsilsesquioxane.
[0096] In the above embodiment, the step of preparing imidazolium-grafted propyl silsesquioxane based on octaiodopropyl silsesquioxane includes: dissolving octaiodopropyl silsesquioxane in N,N-dimethylformamide under a preset environment, adding N-methylimidazole dropwise, reacting at a third preset temperature for a third preset time to obtain a third mixture, and vacuum drying the third mixture to obtain imidazolium-grafted propyl silsesquioxane.
[0097] In this embodiment, octaiodopropyl silsesquioxane is dissolved in N,N-dimethylformamide, and N-methylimidazole is added dropwise, so that the imidazole group can replace the iodine element in the octaiodopropyl silsesquioxane to generate imidazolium-grafted propyl silsesquioxane, and then the N,N-dimethylformamide solvent and excess unreacted imidazole are vacuum dried to obtain imidazolium-grafted propyl silsesquioxane.
[0098] In the above embodiment, the preset environment includes a protective gas environment, and further includes a nitrogen environment.
[0099] In this embodiment, the reaction environment of octaiodopropylsilsesquioxane and N-methylimidazole is controlled to be a nitrogen environment, so as to avoid oxygen doping and reduce the grafting effect.
[0100] In the above embodiment, the third preset temperature is greater than or equal to 50°C and less than or equal to 70°C; the third preset time is greater than or equal to 20h and less than or equal to 48h; further, the third preset temperature is equal to 60°C; the third preset time is equal to 24h.
[0101] In this embodiment, by controlling the reaction temperature and reaction time of octaiodopropylsilsesquioxane and N-methylimidazole, the smooth grafting of imidazole groups can be ensured, and the yield of imidazolium-grafted propylsilsesquioxane can be guaranteed.
[0102] In the above embodiment, the mass ratio of octaiodopropylsilsesquioxane to N-methylimidazole is greater than or equal to 1:15 and less than or equal to 1:3.
[0103] In these technical solutions, the grafting rate of the imidazole group can be ensured by controlling the mass ratio of octaiodopropylsilsesquioxane to N-methylimidazole.
[0104] In the above embodiment, the steps of preparing an anion exchange membrane based on grafted imidazolium propyl silsesquioxane and quaternized polysulfone include: dissolving the grafted imidazolium propyl silsesquioxane in water to obtain an aqueous solution of grafted imidazolium propyl silsesquioxane; dissolving the quaternized polysulfone in an N,N-dimethylformamide solution, adding the aqueous solution of grafted imidazolium propyl silsesquioxane and stirring for a fourth preset time to obtain a fourth mixture, then pouring the fourth mixture into a culture dish, drying at a fourth preset temperature to obtain a composite membrane, and immersing the composite membrane in a potassium hydroxide solution to obtain an anion exchange membrane.
[0105] In this embodiment, the grafted imidazolium propyl silsesquioxane is first dissolved in water to obtain an aqueous solution of the grafted imidazolium propyl silsesquioxane, and then the quaternized polysulfone is dissolved in an N,N-dimethylformamide solution, and the aqueous solution of the grafted imidazolium propyl silsesquioxane is added, and stirred for a fourth preset time to obtain a fourth mixture, at which time the quaternized polysulfone and the grafted imidazolium propyl silsesquioxane are completely mixed, and finally the mixture is dried at a fourth preset temperature to remove the N,N-dimethylformamide solution solvent and water to obtain a complex of the quaternized polysulfone and the grafted imidazolium propyl silsesquioxane, and finally the complex is immersed in a potassium hydroxide solution to obtain an anion exchange membrane.
[0106] In the above embodiment, in the step of drying at the fourth preset temperature, the drying environment is a vacuum environment.
[0107] In the above embodiment, the fourth preset temperature is greater than or equal to 50°C and less than or equal to 70°C; the fourth preset time is greater than or equal to 40h and less than or equal to 72h. Further, the fourth preset temperature is equal to 60°C; the fourth preset time is equal to 48h.
[0108] In this embodiment, controlling the stirring time can make the quaternized polysulfone and the grafted imidazolium propyl silsesquioxane mix evenly, and controlling the drying temperature can ensure that the N,N-dimethylformamide solution solvent and water in the mixture are completely removed to obtain a composite of quaternized polysulfone and grafted imidazolium propyl silsesquioxane.
[0109] In the above embodiment, in the aqueous solution of imidazolium-grafted propyl silsesquioxane, the mass proportion of imidazolium-grafted propyl silsesquioxane is greater than or equal to 5% and less than or equal to 20%. Further, the mass proportion of imidazolium-grafted propyl silsesquioxane is 15%.
[0110] In the above embodiment, in the potassium hydroxide solution, the molar concentration of potassium hydroxide is greater than or equal to 0.5 mol / L and less than or equal to 1.5 mol / L. Further, the molar concentration of potassium hydroxide is 1 mol / L.
[0111] In this embodiment, the concentration of potassium hydroxide is controlled, which can improve the conductivity of the anion exchange membrane.
[0112] In the above-mentioned embodiments, the quaternized polysulfone includes quaternized polysulfone having chloride ions.
[0113] In the above embodiment, the quaternary ammonium polysulfone with chloride ions is prepared by the following method: dissolving the polysulfone in chloroform, adding polyoxymethylene and chlorotrimethylsilane to the chloroform to obtain a fifth mixture, adding tin tetrachloride to the fifth mixture to generate chloromethylated polysulfone; dissolving the chloromethylated polysulfone in N,N-dimethylformamide, and adding triethylamine to the N,N-dimethylformamide to generate a second product, drying the second product, and washing the second product with N,N-dimethylformamide and methanol in sequence to obtain a quaternary ammonium polysulfone with chloride ions.
[0114] In this embodiment, when preparing a quaternary ammonium polysulfone with chloride ions, 22.6 mmol of polysulfone (PSU) can be weighed and transferred to a three-necked flask, dissolved in a certain amount of chloroform to obtain a clear polymer solution, and then a mixture of 226 mmol of paraformaldehyde and 226 mmol of chlorotrimethylsilane is added as a chloromethylating agent, while constantly stirring, in the presence of 2.26 mmol of SnCl4, and reacting at 60°C for 24 hours to generate a large amount of chloromethylated polysulfone product, then using methanol to precipitate and separate the chloromethylated polysulfone product, and then further washing the chloromethylated polysulfone product with water several times until the pH is neutral, and then The product is then dried at 60°C for one day to obtain pure chloromethylated polysulfone. After drying, the chloromethylated polysulfone (CMPSU) is transferred to a three-necked flask and dissolved in an appropriate amount of N,N-dimethylformamide. Triethylamine is added to the solution, and a nitrogen atmosphere is maintained during the entire reaction process. The reaction is carried out at 80°C for about 24 hours to obtain a second product and dry it. After drying, the second product is washed with N,N-dimethylformamide and methanol in sequence to obtain pure quaternized polysulfone. Since the ammonium ions in the triethylamine are paired with the chloride ions in the chloromethylated polysulfone in the quaternization step, the quaternized polysulfone prepared by the present invention is also called quaternized polysulfone with chloride ions. Of course, the paired anions in the quaternized polysulfone can be anions such as sulfonate, and the quaternized polysulfone with chloride ions in the present invention refers to the anions paired with the quaternized polysulfone are chloride ions.
[0115] The structure of quaternized polysulfone with chloride ion is as follows:
[0116]
[0117] In the structural formula, Et3 represents 3 methyl groups; the infrared spectrum is shown in Figure 6 shown.
[0118] See also Figure 2 The second embodiment of the present invention provides a method for preparing an anion exchange membrane, comprising the following steps:
[0119] S202: A mixture containing 300 mL of methanol and 10 mL of HCl (mass fraction of 35%) was added to a 500 mL double-necked round-bottom flask and cooled to 0°C. After 30 minutes, 30 g of (3-chloropropyl)trimethoxysilane was added dropwise, and the mixture was stirred for 2 hours and then allowed to stand for 48 hours. Then, 0.3 g of di-n-butyltin dilaurate catalyst was added, and the reaction mixture was vigorously stirred at 30°C for 2 days to form a white precipitate, which was separated by filtration and washed three times with methanol to remove impurities. Finally, it was vacuum dried at 60°C for 24 hours to obtain Cl-POSS (also known as octachloropropylsilsesquioxane).
[0120] S204: About 5 g of Cl-POSS and 10 g of sodium iodide are dissolved in 100 mL of dry tetrahydrofuran, and the reaction mixture is stirred in the dark at 60°C for 72 hours to completely replace Cl with I, then the tetrahydrofuran is evaporated, and the product is extracted with CHCl3 and H2O, and the organic layer is dried with sodium sulfate and sodium thiosulfate to remove unreacted iodide, and I-POSS (also known as octaiodopropylsilsesquioxane or octa(3-iodopropyl)silsesquioxane) is obtained after distillation.
[0121] S206: About 3 g of I-POSS was dissolved in 50 mL of N,N-dimethylformamide under nitrogen atmosphere, and N-methylimidazole (9 mL) was added dropwise. The reaction was carried out at 60° C. for 24 hours. The reaction mixture was dried under vacuum to evaporate the solvent and excess unreacted imidazole to obtain a yellow sticky solid IM-POSS (i.e., imidazolium-grafted propylsilsesquioxane). Its hydrogen nuclear magnetic resonance spectrum is as follows: Figure 7 As shown in the infrared spectrum Figure 8 As shown in the transmission electron microscopy photograph Fig. 9 shown.
[0122] S208: The quaternized polysulfone with chloride ions is completely dissolved in N,N-dimethylformamide, and 5% IM-POSS is added and stirred for 48 hours, and then the uniform solution is poured into a clean and dry Petri dish, and vacuum dried at 60°C. A composite membrane is obtained by slow evaporation of N,N-dimethylformamide, and the composite membrane is immersed in a 1 mol / L KOH solution to convert it into an anion exchange membrane (recorded as IM-POSS / QPSU 5%).
[0123] See also Figure 3 The third embodiment of the present invention provides a method for preparing an anion exchange membrane, comprising the following steps:
[0124] S302: A mixture containing 60 mL of methanol and 2 mL of HCl (mass fraction of 35%) was added to a 100 mL double-necked round-bottom flask, and the mixture was cooled to 0° C. After 30 minutes, 6 g of (3-chloropropyl)trimethoxysilane was added dropwise, and the mixture was stirred for 2 hours and then left to stand for 48 hours. Then, 0.05 g of di-n-butyltin dilaurate catalyst was added, and the reaction mixture was vigorously stirred at 30° C. for 2 days to form a white precipitate, which was separated by filtration and washed three times with methanol to remove impurities, and finally dried in vacuo at 60° C. for 24 hours to obtain Cl-POSS;
[0125] S304: About 1 g of Cl-POSS and 2 g of sodium iodide were dissolved in 100 mL of dry tetrahydrofuran, and the reaction mixture was stirred in the dark at 60 ° C for 72 hours to completely replace Cl with I, and then the tetrahydrofuran was evaporated and the product was extracted with CHCl3 and H2O. The organic layer was dried with sodium sulfate and sodium thiosulfate to remove unreacted iodide, and octa(3-iodopropyl)silsesquioxane (I-POSS) was obtained after distillation.
[0126] S306: Under a nitrogen atmosphere, about 0.6 g of I-POSS was dissolved in 50 mL of N,N-dimethylformamide, and 9 mL of N-methylimidazole was added dropwise. The reaction was carried out at 60° C. for 24 hours. The reaction mixture was vacuum dried to evaporate the solvent and excess unreacted imidazole to obtain a yellow sticky solid IM-POSS.
[0127] S308: The quaternized polysulfone ionomer of chloride ion is completely dissolved in N,N-dimethylformamide, and 10% IM-POSS is added and stirred for 48 hours, and then the uniform solution is poured into a clean and dry petri dish, and vacuum dried at 60°C. The composite membrane is obtained by slow evaporation of N,N-dimethylformamide, and the composite membrane is immersed in 1 mol / L KOH solution to convert it into an anion exchange membrane (recorded as IM-POSS / QPSU 10%).
[0128] See also Figure 4 The fourth embodiment of the present invention provides a method for preparing an anion exchange membrane, comprising the following steps:
[0129] S402: A mixture containing 60 mL of methanol and 2 mL of HCl (mass fraction of 35%) was added to a 500 mL double-necked round-bottom flask, and the mixture was cooled to 0° C. After 30 minutes, 6 g of (3-chloropropyl)trimethoxysilane was added dropwise, and the mixture was stirred for 2 hours and then left to stand for 48 hours. Then, 0.1 g of di-n-butyltin dilaurate catalyst was added, and the reaction mixture was vigorously stirred at 30° C. for 2 days to form a white precipitate, which was separated by filtration and washed three times with methanol to remove impurities, and finally dried in vacuo at 30° C. for 48 hours to obtain Cl-POSS;
[0130] S404: About 1 g of Cl-POSS and 2 g of sodium iodide were dissolved in 100 mL of dry tetrahydrofuran, and the reaction mixture was stirred in the dark at 60 ° C for 36 hours to completely replace Cl with I, and then the tetrahydrofuran was evaporated and the product was extracted with CHCl3 and H2O. The organic layer was dried with sodium sulfate and sodium thiosulfate to remove unreacted iodide, and octa(3-iodopropyl)silsesquioxane (I-POSS) was obtained after distillation.
[0131] S406: Under a nitrogen atmosphere, about 0.6 g of I-POSS was dissolved in 50 mL of N,N-dimethylformamide, and 9 mL of N-methylimidazole was added dropwise. The reaction was carried out at 60° C. for 48 hours. The reaction mixture was vacuum dried to evaporate the solvent and excess unreacted imidazole to obtain a yellow sticky solid IM-POSS.
[0132] S408: The quaternized polysulfone ionomer of chloride ion is completely dissolved in N, N-dimethylformamide, and 15% IM-POSS is added and stirred for 72 hours, and then the uniform solution is poured into a clean and dry petri dish, and vacuum dried at 60°C, and a composite membrane is obtained by slow evaporation of N, N-dimethylformamide, and the composite membrane is immersed in a 1 mol / L KOH solution to convert it into an anion exchange membrane (recorded as IM-POSS / QPSU 15%). The same method is used to add 20% IM-POSS to obtain an anion exchange membrane IM-POSS / QPSU 20%.
[0133] Comparative Example 1
[0134] This comparative example uses quaternized polysulfone (QPSU) material to prepare an anion exchange membrane, and compared with the embodiment, the IM-POSS doping process is removed. The specific process includes:
[0135] The quaternized polysulfone with chloride ions was completely dissolved in N,N-dimethylformamide, and then the uniform solution was poured into a clean and dry Petri dish and vacuum dried at 60°C. A thin film was obtained by slow evaporation of N,N-dimethylformamide, and the film was immersed in a 1 mol / L KOH solution to convert it into an anion exchange membrane (denoted as QPSU).
[0136] The anion exchange membranes obtained in the above Examples 1 to 3 and Comparative Example 1 were subjected to performance tests:
[0137] 1) Mechanical properties
[0138] The anion exchange membrane (relative humidity 100%) was cut into pieces of 0.5 cm wide and 5 cm long, and stretched at a speed of 10 mm / min using a universal tensile machine. The measurement results were recorded as follows: Fig.10 shown.
[0139] Due to the weak bonding forces between POSS (propyl silsesquioxane) molecules and its compatibility with organic substituents, it can effectively diffuse into the polymer matrix at the molecular level and reinforce the polymer matrix. Enhanced dispersion (nanoscale distribution) was observed in the 10% IM-POSS composite film, which also showed a maximum tensile strength of about 59 MPa. The film containing 15% filler showed a slightly lower strength (52 MPa) due to the initiation of aggregation of inorganic fillers in the film.
[0140] 2) XRD data of anion exchange membrane such as Fig.11 As shown in the figure, with the increase of the addition ratio of filler IM-POSS, the crystallinity of the anion exchange membrane decreases, which is beneficial to ion conduction.
[0141] 3) Electron microscope photos of each anion exchange membrane are as follows Fig.12 As shown, when the filler concentration is between 5% and 15%, the mixing is relatively uniform, but agglomeration tends to occur when the filler concentration exceeds 20%.
[0142] 4) Basic performance of anion exchange membrane
[0143] The OH of the prepared anion exchange membrane was studied using electrochemical impedance spectroscopy. - Conductivity, signal amplitude is 10mV, frequency range is 1MHz to 100Hz. Before measurement, the membrane is soaked in water at 30℃ for 24 hours. The membrane is then sealed between two electrodes and impedance measurement is performed using the two-electrode method.
[0144] The water absorption of the membrane was calculated by the change in membrane weight before and after hydration. A dry membrane with a size of 1 cm × 1 cm was weighed and then immersed in deionized water at room temperature and balanced for 24 hours. After 24 hours, the membrane was quickly weighed after removing the surface water, and the value was recorded to calculate the water absorption of the membrane.
[0145] like Fig.13 As shown, the ionic conductivity of the membrane is high due to the high water absorption and ion exchange capacity of the membrane.
[0146] 5) Performance changes after oxidation test
[0147] The accelerated stability of the composite membranes was tested to investigate the stability of the basic groups present in the polymer chains. The studies were conducted by immersing the membranes in 1 M KOH solution at 60 °C for 7 days. The changes in IEC and conductivity of the membranes after oxidation were measured. Fig.14 As shown, there is no significant change in the performance of the membrane, proving that it has high chemical stability.
[0148] 6) Under the same conditions, the performance of the membranes was compared with that of the membranes in the literature. The results are shown in Table 1 below. The results show that the ion exchange membrane prepared by the present invention has higher ion conductivity and higher working current density, and has excellent performance.
[0149] Table 1
[0150]
[0151] In Table 1, IM-POOSS / QPSU is the anion exchange membrane of the present invention, the base material is QPSU, and the composite material is IM-POOSS; the base material of QPSU / SiO2 and QPSU / ZrO2 is the same as that of the present invention, namely QPSU, and the composite materials are SiO2 and ZrO2, respectively; the base material of PAES / ZrO2 is PAES, and the composite material is ZrO2; the base material of QAPS / PTFE is QAPS, and the composite material is PTFE; in the membranes in Table 1, the addition amount of the composite material is 15%, and the preparation method is consistent with S408 in the embodiment, and only the composite material is changed.
[0152] The invention synthesizes a hydroxyl conductive imidazole group functionalized nano-sized closed-cage silica (T8-POSS), then completely dissolves and blends it with a quaternary ammonium polysulfone polymer with chloride ions, and evaporates the solvent to obtain an ion exchange membrane, thereby improving the alkali resistance stability of the anion exchange membrane in the AEM water electrolysis hydrogen production technology and solving the problem of low power of the quaternary ammonium polysulfone material used in the AEM water electrolysis technology after membrane preparation.
[0153] The anion exchange membranes prepared by the above-mentioned embodiments were tested and found to be able to work stably for at least 7 days in a strong alkaline solution (10 mol / L), while the anion exchange membranes prepared by using quaternized polysulfone (QPSU) materials could only work for 8 hours in a strong alkaline solution. This overcomes the problems of low stability and low power of the anion exchange membranes prepared by using quaternized polysulfone (QPSU) materials in alkaline media.
[0154] An embodiment of the second aspect of the present invention provides an anion exchange membrane. The anion exchange membrane provided by this embodiment is prepared according to the method for preparing an anion exchange membrane provided by any embodiment of the first aspect of the present invention.
[0155] Although this specification includes many specific implementation details, these should not be interpreted as limiting the scope of any invention or the scope of protection claimed, but are mainly used to describe the features of the specific embodiments of specific inventions. Certain features described in multiple embodiments in this specification may also be implemented in combination in a single embodiment. On the other hand, the various features described in a single embodiment may also be implemented separately in multiple embodiments or in any suitable sub-combination. In addition, although features may work in certain combinations as described above and even initially claim protection, one or more features from the claimed combination may be removed from the combination in some cases, and the claimed combination may point to a sub-combination or a variation of a sub-combination.
[0156] Similarly, although operations are depicted in a particular order in the accompanying drawings, this should not be understood as requiring that these operations be performed in the particular order shown or performed sequentially, or requiring that all illustrated operations be performed to achieve the desired results. In some cases, multitasking and parallel processing may be advantageous. In addition, the separation of various system modules and components in the above-described embodiments should not be understood as requiring such separation in all embodiments, and it should be understood that the described program components and systems can generally be integrated together in a single software product, or packaged into multiple software products.
[0157] Thus, specific embodiments of the subject matter have been described. Other embodiments are within the scope of the appended claims. In some cases, the actions recited in the claims can be performed in a different order and still achieve the desired results. In addition, the processes depicted in the drawings do not necessarily require the particular order or sequential order shown to achieve the desired results. In some implementations, multitasking and parallel processing may be advantageous.
[0158] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0159] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A method for preparing an anion exchange membrane, characterized in that: include: Preparation of octachloropropylsilsesquioxane; preparing octaiodopropyl silsesquioxane based on the octachloropropyl silsesquioxane; preparing imidazolium-grafted propyl silsesquioxane based on the octaiodopropyl silsesquioxane; The anion exchange membrane is prepared based on the imidazolium-grafted propylsilsesquioxane and quaternized polysulfone.
2. The method for preparing an anion exchange membrane according to claim 1, characterized in that: The step of preparing octachloropropylsilsesquioxane comprises: Methanol and hydrochloric acid solution are mixed to obtain a first mixture, the first mixture is cooled to a first preset temperature, 3-chloropropyltrimethoxysilane and a catalyst are added to the first mixture, and the mixture is stirred for a first preset time to obtain a generated precipitate, and the precipitate is washed with methanol to obtain the octachloropropyl silsesquioxane.
3. The method for preparing an anion exchange membrane according to claim 2, characterized in that: The first preset temperature is greater than or equal to 0°C and less than or equal to 5°C; The first preset duration is greater than or equal to 40 hours and less than or equal to 60 hours.
4. The method for preparing an anion exchange membrane according to claim 2, characterized in that: The catalyst includes di-n-butyltin dilaurate.
5. The method for preparing an anion exchange membrane according to claim 2, characterized in that: The mass ratio of the catalyst to the 3-chloropropyltrimethoxysilane is greater than or equal to 1:120 and less than or equal to 1:
60.
6. The method for preparing an anion exchange membrane according to claim 2, characterized in that: In the hydrochloric acid solution, the mass fraction of hydrochloric acid is greater than or equal to 30% and less than or equal to 40%.
7. The method for preparing an anion exchange membrane according to claim 1, characterized in that: The step of preparing octaiodopropyl silsesquioxane based on the octachloropropyl silsesquioxane comprises: The octachloropropyl silsesquioxane and iodine salt are dissolved in tetrahydrofuran to obtain a second mixture, and the second mixture is continuously stirred for a second preset time under a second preset temperature condition, and the tetrahydrofuran in the second mixture is evaporated to obtain a first product, and the octaiodopropyl silsesquioxane is extracted from the first product.
8. The method for preparing an anion exchange membrane according to claim 7, characterized in that: The step of extracting the octaiodopropylsilsesquioxane from the first product comprises: The first product is put into a mixed solution of chloroform and water to form an organic layer and an aqueous layer, the organic layer is separated and passed through a column of a mixture of sodium sulfate and sodium thiosulfate to remove chloroform in the organic layer, and the octaiodopropylsilsesquioxane is obtained.
9. The method for preparing an anion exchange membrane according to claim 7, characterized in that: The iodized salt is sodium iodide.
10. The method for preparing an anion exchange membrane according to claim 9, characterized in that: The mass ratio of the octachloropropylsilsesquioxane to the sodium iodide is greater than or equal to 1:3 and less than or equal to 1:
1.
11. The method for preparing an anion exchange membrane according to claim 7, characterized in that: The second preset temperature is greater than or equal to 50° C. and less than or equal to 70° C.; The second preset duration is greater than or equal to 60 hours and less than or equal to 80 hours.
12. The method for preparing an anion exchange membrane according to claim 7, characterized in that: The step of continuously stirring the second mixture for a second preset time period under the condition of the second preset temperature is performed in a closed environment without any light.
13. The method for preparing an anion exchange membrane according to claim 1, characterized in that: The step of preparing imidazolium-grafted propyl silsesquioxane based on the octaiodopropyl silsesquioxane comprises: Under a preset environment, the octaiodopropyl silsesquioxane is dissolved in N,N-dimethylformamide, and N-methylimidazole is added dropwise, and the mixture is reacted at a third preset temperature for a third preset time to obtain a third mixture, and the third mixture is vacuum dried to obtain the imidazolium-grafted propyl silsesquioxane.
14. The method for preparing an anion exchange membrane according to claim 13, characterized in that: The preset environment includes a protective gas environment.
15. The method for preparing an anion exchange membrane according to claim 13, characterized in that: The third preset temperature is greater than or equal to 50° C. and less than or equal to 70° C.; The third preset duration is greater than or equal to 20 hours and less than or equal to 48 hours.
16. The method for preparing an anion exchange membrane according to claim 13, characterized in that: The mass ratio of the octaiodopropylsilsesquioxane to the N-methylimidazole is greater than or equal to 1:15 and less than or equal to 1:
3.
17. The method for preparing an anion exchange membrane according to claim 1, characterized in that: The step of preparing the anion exchange membrane based on the grafted imidazolium propyl silsesquioxane and quaternized polysulfone comprises: dissolving the imidazolium-grafted propyl silsesquioxane in water to obtain an aqueous solution of the imidazolium-grafted propyl silsesquioxane; The quaternized polysulfone is dissolved in an N,N-dimethylformamide solution, and an aqueous solution of the grafted imidazolium propylsilsesquioxane is added, and stirred for a fourth preset time to obtain a fourth mixture, and then the fourth mixture is poured into a culture dish, and dried at a fourth preset temperature to obtain a composite membrane, and the composite membrane is immersed in a potassium hydroxide solution to obtain the anion exchange membrane.
18. The method for preparing an anion exchange membrane according to claim 17, characterized in that: In the step of drying at the fourth preset temperature, the drying environment is a vacuum environment.
19. The method for preparing an anion exchange membrane according to claim 18, characterized in that: The fourth preset temperature is greater than or equal to 50° C. and less than or equal to 70° C.; The fourth preset duration is greater than or equal to 40 hours and less than or equal to 72 hours.
20. The method for preparing an anion exchange membrane according to claim 17, characterized in that: In the aqueous solution of the imidazolium-grafted propyl silsesquioxane, the mass proportion of the imidazolium-grafted propyl silsesquioxane is greater than or equal to 5% and less than or equal to 20%.
21. The method for preparing an anion exchange membrane according to claim 20, characterized in that: In the aqueous solution of the imidazolium-grafted propyl silsesquioxane, the mass proportion of the imidazolium-grafted propyl silsesquioxane is 15%.
22. The method for preparing an anion exchange membrane according to claim 17, characterized in that: In the potassium hydroxide solution, the molar concentration of potassium hydroxide is greater than or equal to 0.5 mol / L and less than or equal to 1.5 mol / L.
23. The method for preparing an anion exchange membrane according to claim 17, characterized in that: The quaternized polysulfone includes quaternized polysulfone having chloride ions.
24. The method for preparing an anion exchange membrane according to claim 23, characterized in that: The quaternized polysulfone with chloride ions is prepared by the following method: dissolving polysulfone in chloroform, adding polyoxymethylene and chlorotrimethylsilane to the chloroform to obtain a fifth mixture, and adding tin tetrachloride to the fifth mixture to generate chloromethylated polysulfone; The chloromethylated polysulfone is dissolved in N,N-dimethylformamide, and triethylamine is added to the N,N-dimethylformamide to generate a second product. The second product is dried, and the second product is washed with N,N-dimethylformamide and methanol in sequence to obtain the quaternary ammonium polysulfone with chloride ions.
25. An anion exchange membrane, characterized in that: The anion exchange membrane is prepared by the method for preparing anion exchange membrane according to any one of claims 1 to 24.